EFFECTIVE WAYS FOR ENGLISH LEARNERS (American Journal of Interdisciplinary Research and Development, 2024)
English language learners (ELLs) face a multifaceted journey toward achieving proficiency in their second language. This abstract synthesizes research on effective strategies for facilitating English language acquisition, providing insights for educators, policymakers, and learners themselves. We explore a range of strategies tailored to the diverse needs and backgrounds of ELLs. First, we examine language acquisition theory, emphasizing the importance of meaningful input, interaction, and feedback in language learning environments. Next, we discuss the role of motivation in driving language acquisition efforts, highlighting the significance of intrinsic and extrinsic factors in sustaining learners' engagement and perseverance.